THE METATRON-SANDALPHON MECHANISM: A HYPOTHETICAL COSMIC ENGINEERING FRAMEWORK - Michael William Pratama Wenas (Integrative Perspectives of Social and Science Journal, 2026)
Theoretical study of the Metatron-Sandalphon Mechanism as a hypothetical cosmological engineering model to explain the potential slowing of the universe's accelerated expansion. The model is divided into two phases: the Metatron Mechanism, which posits the development of dark sector particles called scotons along cosmic filament structures, later converted into lepton pairs that generate local gravitational pressure to counteract dark energy, and the Sandalphon Mechanism, which explains how the energy from this process is absorbed and crystallized into stable matter to prevent vacuum instability. To model these dynamics, the study uses Python-based quantum computing simulations with IBM Qiskit, supplemented by continuous-time Markov probability chains. The quantum circuit topologies are designed based on esoteric geometric heuristics, specifically Metatron’s Cube and the layered Hexahedron structure, to simulate the spread of the expansion-halting wave and the collapse of energy into dense baryonic states. The results demonstrate a computationally feasible path from an accelerating universe to a stagnant, crystallized state, accompanied by space-time stratification, causal disconnections, and potential high-energy phenomenological signatures.